Maintaining the Existence of Wayang Golek Punakawan Sunda through Photography - Sabilla, Noviana; Sari, Maya Purnama (Institut Seni Indonesia Surakarta, 2021)
Wayang Golek is one of the nation's cultural heritage that grows and develops in West Java, and its existence still exists today but is starting to decline. Photography is one part of the technology that can bridge the Punakawan Sundanese Wayang Golek Culture in maintaining its existence. The purpose of the research is to maintain the existence of the Punakawan Sundanese Wayang Golek Culture through the media of Photography. The research method uses a qualitative descriptive approach obtained through interviews, observations and is equipped with photographic works. The results of this study indicate that Photography can be one of the media in maintaining the existence of Wayang Golek, especially the Sundanese Punakawan group, through social media such as Instagram. Photography by researchers and other artists' works shared via Instagram can be spread worldwide and stored forever, with periodic and continuous stages, the existence of Wayang Golek, especially Punakawan Sundanese, will be maintained.Keywords: Art Fotografi; Punakawan;Culture Wayang Golek.